Transcultural and Transcontinental Telecollaboration for Foreign Language Learning: proposals and challenges - Costa, Leila Martins Gonçalves da; Salomão, Ana Cristina Biondo; Zakir, Maisa de Alcântara (Revista do GEL, 2018)
.